PROPHYLAXIS OF THE PAIN OF THE SYNDROME WHEN USING REMOVABLE DENTURES - M.Ya. Nidzelsky; N.V. Tsvetkova; V.M. Sokolovskaya (Ukrainian Medical Stomatological Academy, 2017)
Orthopedic dental treatment can be accompanied by pain of a different nature, a violation of sensitivity and the appearance of various paresthesias (burning, itching, tingling, numbness, etc.). Dentures are an irritant for the tissues of the oral cavity, namely, its excessive pressure in certain areas of the prosthetic bed. It is well known that a large number of patients using removable dentures can not get used to them because of the pain. The basis of our research is the goal of improving the method of preventing pain syndrome with the use of removable dentures, whereby by making changes to the special preparation for prosthetics and the means of preventing inflammatory conditions, conditions are created to prevent the pain syndrome and increase the sensitivity threshold of the mucous membrane of the prosthetic field. Materials and methods. The study took part 12 patients with complete removable dentures for the upper and lower jaw. Patients noted a poor fixation, pain when using dentures. The task is solved by the use of electro-diagnostics of tissues dentition method of R. Voll that determine the pain threshold mucosa alveolar process and palate. Then determine the acupuncture point area earlobe. Mikroholkoterapiyu conduct continuous exposure to a group of acupuncture points, duration of exposure 7 days. With prolonged use acupuncture needles mikroholkoterapiyi buttons will be increased threshold mucosal prosthetic field to prevent pain (pain) in orthopedic treatment using removable dentures. Established R. Voll measuring point can determine the status of land together mucosa, tooth device connected to its corresponding fragment and alveolar bone of the jaw. Electro-diagnostic apparatus performing "Biotest" principle of the device is based on the measurement of biologically active points of resistance of the skin and mucous membranes, measured in arbitrary units of the device. The results of electrical measurements points made in the examination of patients on map existing standard power band in electro diagnostics. After identifying pain points auricular mikroholkoterapiyu conduct. Patients who first used aurykuloterapiyu sessions should be done in a prone position. Put classical way special needle-button on the acupuncture points of the ear. Compared with microneedles for koporalnyh points they are smaller, and core needle perpendicular branches handle. Mikroholkoterapiyu hold cycles, namely continuous exposure to a group of acupuncture points. Cycle time 7 days because used needles with silver. Then take a break between cycles of 5 days. To achieve meaningful clinical effect and to consolidate the results obtained conduct 3 courses mikroholkoterapiyi acupuncture. Each cycle is carried out by electro diagnostics R. Voll. After lowering the pain threshold mucosa alveolar process and palate in the most typical areas of pressure, hold prostheses removable dentures.Simultaneously were produced full dentures on the upper and lower jaw. Correction and sdacha prosthesis was performed on the day of graduation acupuncture mikroholkoterapiyi According to the results of the study, it was found that the use of auricular microhole therapy, carried out by cycles of 7 days, with an interval of 5 days, leads to a decrease in pain sensitivity of the mucous membrane of the alveolar processes and palate to the norm parameters, which in turn significantly reduces and facilitates the period of adaptation to complete removable prostheses.